Characterising shoot and root system trait variability and contribution to genotypic variability in juvenile cassava (Manihot esculenta Crantz) plants. Issue 6 (June 2018) - Adu, Michael Osei; Asare, Paul Agu; Asare-Bediako, Elvis; Amenorpe, Godwin; Ackah, Frank Kwekucher; Afutu, Emmanuel; Amoah, Mishael Nyarko; Yawson, David Oscar
Abstract: The development of cassava genotypes with root system traits that increase soil resource acquisition could increase yields on infertile soils but there are relatively few work that has quantified cassava root system architecture (RSA). We used an easily adaptable and inexpensive protocol to: (i) measure genotypic variation for RSA and shoot traits of a range of cassava genotypes; and (ii) identify candidate variables that contribute the largest share of variance. Cassava genotypes were grown in soil-filled pots, maintained at 70% field capacity. Shoot and RSA traits were measured on plants grown up to 30, 45 and 60 days. Multivariate analysis was used to determine major traits contributing to variation. The study showed that cassava roots are adventitious in origin consisting of a main root axis and orders of lateral roots, and therefore the historically used term "fibrous roots" are redundant currently not contributing to clarity. There were significant differences ( P < 0.05) for traits evaluated. The highest relative root growth rate occurred over the first 30 days and ranged from 0.39 to 0.48 cm day −1 . Root fresh weight was significantly correlated with other traits, including root length ( r = 0.79), leaf area ( r = 0.72), number of lower nodal roots ( r = 0.60), indicating that direct selection based on these traits might be sufficient to improve root biomass. Up to the first six principal components explained over 80% of the total variation among the genotypes for the traits measured at 30, 45 and 60 days. Leaf area, root diameter and branching density-related traits were the most important traits contributing to variation. Selection of cassava genotypes based on shoot and root biomass, root diameter and branching density at juvenile growth stage could be successful predictors of nutrient and water-use efficiency in the field. Further studies are required to relate studied juvenile cassava root traits with the performance of field-grown-mature plant with regard to drought, nutrient-use efficiency and yield.